DETERMINANTS RELATED TO KNOWLEDGE OFFERTILE WOMEN (WUS) ON THE TRANSMISSION OF HIV/AIDS FROM MOTHER TO INFANT IN INDONESIA (ADVANCED ANALYSIS OF 2017 IDHS DATA) - Elvira Nova Riany; Farrah Fahdhienie; Nopa Arlianti (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: HIV/AIDS infection in pregnant women can threaten the life of the mother and can transmit it to her baby. Lack of knowledge regarding the transmission of HIV/AIDS from mother to baby, will further increase the risk of transmission which will affect the increase in new cases. The aims of the study was to determine the relationship between residence, education level, marital status, employment status, exposure to information sources, and welfare index, as well as to determine the factors that most influence the knowledge of women of childbearing (WUS) about the transmission of HIV/AIDS from mother to baby. Methods: Using analytic survey data a cross-sectional study design. The population in this study were WUS in 34 Provinces in Indonesia. The sample selection was based on ratio using used stratification and multistage random sampling. The sample in this study were all WUS in Indonesia who had heard about HIV/AIDS. Data was collected by observating the 2017 IDHS data. The data were analyzed using multivariate logistic regression. Result: The only variables related to knowledge about the transmission of HIV/AIDS from mother to baby are place of residence and welfare index, while other variables: education level, marital status, employment status, and information sources have no relationship. Residence and welfare index are the most influential variables. Recommendation: To increase knowledge about the transmission of HIV/AIDS from mother to baby, by involving related institutions that have authority to formulate policies to increase WUS knowledge.